2019
DOI: 10.1039/c9qm00246d
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-nanotube-filled catalyst-free thermoset polyurea composites towards achieving recyclability, weldability and permanent shape reconfiguration

Abstract: The incorporation of carbon nanotubes into catalyst-free thermoset polyurea composites can achieve their excellent reprocessability by hot press or micro injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…These HTPUs were synthesized through a facile route reported in our previous study . The synthesized secondary amine of HDLA-100 was dissolved in the solvent of anhydrous ethyl acetate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These HTPUs were synthesized through a facile route reported in our previous study . The synthesized secondary amine of HDLA-100 was dissolved in the solvent of anhydrous ethyl acetate.…”
Section: Methodsmentioning
confidence: 99%
“…These HTPUs were synthesized through a facile route reported in our previous study. 39 The synthesized secondary amine of HDLA-100 was dissolved in the solvent of anhydrous ethyl acetate. A stoichiometric amount of IPDI was slowly added into HDLA-100 solution in the absence of catalyst.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…28,29 Jiang et al synthesized carbon nanotube-filled thermoset PU composites with a shape memory recovery rate of 90% under heat or NIR irradiation, based on hindered urea bonding to achieve integrated recyclability, weldability, and permanent shape reconfiguration. 30,31 Zhang et al reported a multirecyclable shape memory supramolecular PU. 32 However, the tensile strength and toughness of the PU have not been systematically studied.…”
Section: Introductionmentioning
confidence: 99%
“…Polyurea (PU) is an attractive industrial material for industrial primers or protective coatings because of impact resistance, excellent ductility, and excellent friction resistance mechanical properties. , Jiang et al synthesized carbon nanotube-filled thermoset PU composites with a shape memory recovery rate of 90% under heat or NIR irradiation, based on hindered urea bonding to achieve integrated recyclability, weldability, and permanent shape reconfiguration. , Zhang et al reported a multirecyclable shape memory supramolecular PU . However, the tensile strength and toughness of the PU have not been systematically studied.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure h, the XRD curves of OC-8K and CNT@PCMs show two strong diffraction peaks near 19.4° and 23.5°, which correspond to the crystal planes (120) and (112), respectively. The XRD results showed that the intensity and position of the XRD peak of OC-8K and CNT@PCMs had little change, indicating that the addition of CNTs has no significant effect on the crystallization property and crystal shape of CNT@PCMs . According to Figure i,j and Table , the melting (Δ H m ) and freezing (Δ H f ) latents of OC-8K were 97.8 and 93.9 J g –1 , respectively, and the melting ( T m ) and freezing ( T f ) points of OC-8K were 42.9 and 38.7 °C, respectively.…”
Section: Results and Discussionmentioning
confidence: 98%